2021
DOI: 10.1007/s10854-021-06565-3
|View full text |Cite
|
Sign up to set email alerts
|

Constructing BiOBr/g-C3N4/Bi2O2CO3 Z-scheme photocatalyst with enhanced photocatalytic activity

Abstract: Novel camellia-structured Z-scheme BiOBr/g-C 3 N 4 /Bi 2 O 2 CO 3 was simply prepared by a hydrothermal method and photodegraded Rhodamine B under visible light within 60 min with much higher degradation e ciency (98%) contrasted with pure BiOBr, g-C 3 N 4 and Bi 2 O 2 CO 3 . Radical trapping experiments exhibited the main reactive species (•O 2 -) during degradation process. The formation of Z-scheme heterojunction improved rate of charge separation, enhanced absorption of visible light and thus promoted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Thus, if BiOBr/g-C 3 N 4 adopts the band-band transfer, O 2 À and OH could not be formed. On the other hand, the Z-scheme mechanism 21,35,37,41 and the S-scheme mechanism 42,43 have also been reported. However, the solid experimental evidence needs to be further verified deeply and comprehensively, especially combining theoretical calculations with in situ X-ray photoelectron spectrometry (in situ XPS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if BiOBr/g-C 3 N 4 adopts the band-band transfer, O 2 À and OH could not be formed. On the other hand, the Z-scheme mechanism 21,35,37,41 and the S-scheme mechanism 42,43 have also been reported. However, the solid experimental evidence needs to be further verified deeply and comprehensively, especially combining theoretical calculations with in situ X-ray photoelectron spectrometry (in situ XPS).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, BiOBr/g-C 3 N 4 heterostructure has been widely reported for pollutant degradation due to its good photocatalytic activity and stability. 17–43 However, the separation and transfer mechanism of photoexcited electrons and holes is a controversial issue. For example, some references 17,24,31 reported that the enhanced photocatalytic activity of BiOBr/g-C 3 N 4 is attributed to the band–band transfer mechanism (the photoexcited electrons on the CB of g-C 3 N 4 are transferred into the CB of BiOBr, and the photoexcited holes on the VB of BiOBr are transferred into the VB of g-C 3 N 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…7b, the band gaps of CdS, BSC, and BOC were 2.20, 3.30, and 3.36 eV, respectively. The VB and CB potentials of the semiconductor were determined by eqn (2) and (3): 48 E VB = X − Ee + 0.5Eg E CB = E VB − Egwhere Ee is the free energy under the hydrogen standard, E CB is the conduction band potential, X is the electronegativity of the material, and E VB is the valence band potential. The X values of CdS, BSC, and BOC were 5.05, 6.54, and 6.33 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…values of CdS, BSC, and BOC were 5.05, 6.54, and 6.33 eV, respectively. 31,[47][48][49] The E VB values of CdS, BSC, and BOC were calculated to be 1.65, 3.69, and 3.51 eV, and their E CB values were calculated to be −0.55, 0.39, and 0.15 eV, respectively. Reaction Chemistry & Engineering Paper…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…15,28 Bi 2 O 2 CO 3 as a typical layered structure photocatalyst has been widely investigated in wastewater purification. [29][30][31] To enhance the activity, various semiconductors have been applied to couple with Bi 2 O 2 CO 3 , such as BiOCl, [32][33][34] Bi 2 O 3 , [35][36][37] C 3 N 4 , [38][39][40] etc. Sun et al discovered that the photoactivity for degrading typical pollutants (such as rhodamine B, phenol, and bisphenol A) under visible light was significantly improved by constructing a type II scheme Bi 2 O 2 CO 3 /Bi 2 O 4 heterojunction.…”
Section: Introductionmentioning
confidence: 99%